Diagnosis of beef production systems for meat in Tejupilco, State of Mexico - Rodríguez Mejía, Sergio; Flores Sánchez, Diego; León Merino, Aurelio; Pérez Hernández, Luz María; Aguilar Ávila, Jorge (Revista Mexicana de Ciencias Agrícolas, 2018)
In Mexico, cattle ranching is the second most widespread productive activity in rural areas after agriculture, its importance lies in generating self-employment in the rural sector. In the municipality of Tejupilco, State of Mexico, there are 1 839 beef cattle producers, who contribute 30% of the meat production of the Tejupilco district and 14.9% statewide. Currently, there is an information gap that allows to know the conditions in which producers of cattle for meat in the municipality are immersed. The objective of the research was to diagnose beef production systems for meat from two communities in the municipality of Tejupilco, and identify alternatives for improvement. The methodological approach contemplated the application of a structured questionnaire in three thematic axes: 1) socioeconomic profile and available resources of the family; 2) socioeconomic and agronomic indicators; and 3) productive technical management of beef cattle. The production of cattle for meat is very diverse in terms of available resources, technical productive management; the lack of technical training and financial resources, and an inefficient organization are widespread, manifesting themselves in a technical-productive backwardness and dependence on external inputs. It is recommended to establish a training and accompaniment program that addresses the main limitations encountered.
Keywords: characterization; bovine meat system; indicators